Gadolinium Oxide Nanoparticles as Potential Multimodal Imaging and Therapeutic Agents - Jeong Kim, Tae; Seok Chae, Kwon; Chang, Yongmin; Ho Lee, Gang (Current Topics in Medicinal Chemistry, 2013)
Potentials of hydrophilic and biocompatible ligand coated gadolinium oxide nanoparticles as multimodal imaging agents, drug carriers, and therapeutic agents are reviewed. First of all, they can be used as advanced T1 magnetic resonance imaging (MRI) contrast agents because they have r1 larger than those of Gd(III)-chelates due to a high density of Gd(III) per nanoparticle. They can be further functionalized by conjugating other imaging agents such as fluorescent imaging (FI), X-ray computed tomography (CT), positron emission tomography (PET), and single photon emission tomography (SPECT) agents. They can be also useful for drug carriers through morphology modifications. They themselves are also potential CT and ultrasound imaging (USI) contrast and thermal neutron capture therapeutic (NCT) agents, which are superior to commercial iodine compounds, air-filled albumin microspheres, and boron (10B) compounds, respectively. They, when conjugated with targeting agents such as antibodies and peptides, will provide enhanced images and be also very useful for diagnosis and therapy of diseases (so called theragnosis).
Keywords: MRI